2016
DOI: 10.1111/add.13270
|View full text |Cite
|
Sign up to set email alerts
|

Association between trajectories of buprenorphine treatment and emergency department and in‐patient utilization

Abstract: Six distinct buprenorphine treatment trajectories were identified in this population-based low-income Medicaid cohort in Pennsylvania, USA. There appears to be an association between persistent use of buprenorphine for 12 months and lower risk of all-cause hospitalizations/emergency department visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 54 publications
4
96
0
Order By: Relevance
“…Although a trend, patients with persistent use of buprenorphine were less likely to use the ED, with one interpretation being that they were more stable in terms of their health and in less need of ED services. This is consistent with prior literature, and in addition to improved patient outcomes, would be a benefit to health systems (Schwarz et al 2012; Lo-Ciganic et al 2016; Tkacz et al 2014). Although it is not possible with the present data, it is important to examine the relationship of persistent use of buprenorphine over the longer term to services utilization and other outcomes, since little is known about patients who use buprenorphine over the long term.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although a trend, patients with persistent use of buprenorphine were less likely to use the ED, with one interpretation being that they were more stable in terms of their health and in less need of ED services. This is consistent with prior literature, and in addition to improved patient outcomes, would be a benefit to health systems (Schwarz et al 2012; Lo-Ciganic et al 2016; Tkacz et al 2014). Although it is not possible with the present data, it is important to examine the relationship of persistent use of buprenorphine over the longer term to services utilization and other outcomes, since little is known about patients who use buprenorphine over the long term.…”
Section: Discussionsupporting
confidence: 91%
“…However, patients with OUD who are maintained on buprenorphine may have higher functioning and improved health, and potentially more appropriate use of health services. For example, three recent studies indicated that patients with longer retention on buprenorphine had lower likelihood of using expensive services such as the ED and hospitalizations (Schwarz et al 2012; Lo-Ciganic et al 2016; Tkacz et al 2014). Thus, while buprenorphine patients are likely to have multiple health service needs, effective OUD treatment could lead to lower service utilization over time.…”
Section: Introductionmentioning
confidence: 99%
“…The median treatment duration (53 days) was lower than expected given clinical recommendations of maintenance treatment for up to 12 months 3 and evidence linking longer treatment to better outcomes. 1,4 The findings are limited in that prescriber waiver status is unknown as is patient clinical status; we cannot exclude the possibility that buprenorphine was prescribed off-label for pain.…”
Section: Discussionmentioning
confidence: 94%
“…Achieving OBOT veteran status is important as there are significant benefits associated with remaining on buprenorphine for at least one year, including decreased opioid use,(Hser et al, 2016) as well as decreased hospitalizations and emergency department visits. (Lo-Ciganic et al, 2016) Additionally, patients in recovery from heroin use for at least one year report improved quality of life. (Best et al, 2012)…”
Section: 0 Discussionmentioning
confidence: 99%